Immunotherapy with Tolerogenic Dendritic Cells Alone or in Combination with Rapamycin Does Not Reverse Diabetes in NOD Mice. (11th March 2013) - Pujol-Autonell, Irma; Ampudia, Rosa M.; Monge, Pau; Lucas, Anna M.; Carrascal, Jorge; Verdaguer, Joan; Vives-Pi, Marta
Abstract : Type 1 diabetes is a metabolic disease caused by autoimmunity towards β -cells. Different strategies have been developed to restore β -cell function and to reestablish immune tolerance to prevent and cure the disease. Currently, there is no effective treatment strategy to restore endogenous insulin secretion in patients with type 1 diabetes. This study aims to restore insulin secretion in diabetic mice with experimental antigen-specific immunotherapy alone or in combination with rapamycin, a compound well known for its immunomodulatory effect. Nonobese diabetic (NOD) mice develop spontaneous type 1 diabetes after 12 weeks of age. Autologous tolerogenic dendritic cells—consisting in dendritic cells pulsed with islet apoptotic cells—were administered to diabetic NOD mice alone or in combination with rapamycin. The ability of this therapy to revert type 1 diabetes was determined by assessing the insulitis score and by measuring both blood glucose levels and C-peptide concentration. Our findings indicate that tolerogenic dendritic cells alone or in combination with rapamycin do not ameliorate diabetes in NOD mice. These results suggest that alternative strategies may be considered for the cure of type 1 diabetes.